Tobacco BY-2 Media Component Optimization for a Cost-Efficient Recombinant Protein Production - Häkkinen, Suvi T.; Reuter, Lauri; Nuorti, Ninni; Joensuu, Jussi J.; Rischer, Heiko; Ritala, Anneli (Frontiers in Plant Science, 2018)
Plant cells constitute an attractive platform for production of recombinant proteins as more and more animal-free products and processes are desired. One of the challenges in using plant cells as production hosts has been the costs deriving from expensive culture medium components. In this work, the aim was to optimize the levels of most expensive components in the nutrient medium without compromising the accumulation of biomass and recombinant protein yields. Wild-type BY-2 culture and transgenic tobacco BY-2 expressing GFP-Hydrophobin I (GFP-HFBI) fusion protein were used to determine the most inexpensive medium composition. One particularly high-accumulating BY-2 clone, named ‘Hulk’, produced 1.1±0.2 g/l GFP-HFBI in suspension and kept its high performance during prolonged subculturing. In addition, both cultures were successfully cryopreserved enabling truely industrial application of this plant cell host. With the optimized culture medium, 43-55 % cost reduction in regards to biomass and up to 69 % reduction in regards to recombinant protein production was achieved.